Ethno-Parenting: A Model of Child Rearing Based on Local Malay Wisdom in Teluk Melano Village, Kayong Utara Regency - Syamsul Kurniawan; Utin Darma Ranti; Maimunah (PERADA, 2025)
This study aims to explore and understand the child-rearing model based on local Malay wisdom in Teluk Melano Village, Kayong Utara Regency. The primary focus of this research is to examine how the local community preserves and applies child-rearing practices rooted in traditional values passed down through generations. A phenomenological approach is used in this study to delve into the experiences and meanings embedded in the child-rearing practices within this Malay community. Data were collected through participatory observation and in-depth interviews with community leaders, religious figures, and family members. The findings reveal that values such as mutual cooperation, respect for parents, and moral teachings through customs, taboos, and folklore play significant roles in shaping children's character. Traditions such as Tijak Tanah, Belamin, Berzanji, and folk tales like Pohon Pisang Jerenang and Tok Bubot are not only cultural rituals but also serve as vehicles for moral and social education. This research contributes to the introduction of the ethno-parenting model as a relevant and adaptable child-rearing alternative amidst modernity. The significance of this study lies in the need to preserve local wisdom in child-rearing to strengthen cultural identity and enhance the quality of character education in the future.